A Bibliometric Analysis of Accounting in the Blockchain Era - Mia Ika Rahmawati; Anang Subardjo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to conduct a comprehensive accounting and blockchain analysis with a bibliometric study.Design/Methodology/Approach: The sample consisted of 67 documents published in the 2017-2021 period using the Scopus database with keywords: accounting and blockchain. This study utilized VOSviewer software to provide graphical analysis of bibliometric data and visualization of research results.Research findings: From the visualization, three main groups (colors) of nine clusters were generated. The red area consists of topics related to blockchain technology, ledger technology, and Bitcoin. The green cluster area includes keywords related to the application and the design science research methodology. Lastly, the blue area focuses on accountants and millennial accountants. From the network analysis results, it can be stated that accountants and millennial accountants accepted the presence of blockchain technology. They could integrate blockchain into the company's business model and make their work easier. From these findings, a research methodology emerged, especially in conducting blockchain research, namely the design science research approach.Theoretical contribution/Originality: With the new and hyped topic of blockchain in the accounting sphere, the bibliometric analysis would be able to review multiple studies efficiently and offer a systematic, transparent, and replicable literature review. Also, it guides researchers to the most influential works and maps areas of research with less subjective bias. Besides, it enables analysis more objectively and reliably and improves the quality of the review.